Germination, vigor and pathogen incidence in broccoli seeds treated with Carboxin + Thiram - Cardoso, Antonio Ismael Inácio [UNESP]; Lima, Lanna Natália Brito [UNESP]; Silva, Priscilla Nataly de Lima [UNESP]; Nakada-Freitas, Pâmela Gomes [UNESP]; Santos, Paula Leite dos [UNESP]; Pierozzi, Caroline Geraldi [UNESP]; Kronka, Adriana Zanin [UNESP] (Academic Journals, 2015)
The purpose of treating seeds chemically is to eradicate their pathogens and/or protect them against soil pathogens, mainly by germination time. However, there is little research on vegetables investigating the effect of this treatment on seed quality. Therefore, this study evaluates the effects of Carboxin + Thiram doses on germination and vigor of three lots of broccoli seeds, as well as on the incidence of fungi in treated seed. The 15 treatments were evaluated in a factorial system (3x5), with the first factor consisting of three lots of 'Avenger' broccoli seeds (lots 82744, 82745 and 82749), and the second factor consisting of five doses (0, 0.04, 0.06, 0.10 and 0.12% of a.i.) of Carboxin + Thiram fungicide (commercial name Vitavax-Thiran). The germination and seed vigor were evaluated, in addition to the presence of pathogens in seeds after treatment (blotter test). All lots showed high levels of germination and vigor. The lot 82749, however, showed higher value in plug test in substrate emergence (99%) than lot 82745 (95%). Regarding the treatment with Carboxin + Thiram, no changes in germination average (98%) and vigor were noticed (average for the first germination count, length, and dry weight of seedling, plug test at 10 days after sowing of 97%, 4.9 cm, 4.0 mg and 96%, respectively), showing that this fungicide, in the evaluated doses, does not affect the quality of broccoli seeds. As to seeds health, the pathogens Alternaria spp. and Fusarium spp. were detected, in addition to saprophytic species such as Penicillium, Aspergillus, Trichoderma, and Rhizopus. The higher incidence of Fusarium spp. was noticed in lot 82744, and the lowest in lot 82749. As to Penicillium spp., lot 82479 was the most contaminated. Regarding other fungi, the general incidence was very low and there was no difference between lots and doses used.
Keywords: Brassica oleracea; Seed treatment; Fungicides